Language mixing in the social network of a South African student. Issue 1 (5th May 2020) - Botha, Werner; Coetzee‐Van Rooy, Susan
Abstract: This article discusses the dynamics underlying a particular feature of South African Englishes – language mixing – and how such mixing practices and the use of English form part of the social identity of interactions between speakers in their respective social networks. The approach to this current study was adapted from Milroy's (1980) research on social networks in order to provide access to participants' most natural use of languages. This study investigates various aspects of the multilingual language practices of speakers in South Africa and reports on the social motivations and the social contexts of language mixing in the personal lives of these speakers.